Contentious liberties: American abolitionists in post-emancipation Jamaica, 1834 - 1866 - Kenny, Gale L. (Race in the Atlantic world, 1700 - 1900, 2010)
Revivals, antislavery, and Christian liberty -- Slavery and freedom in Jamaica -- Religion and the civilizing mission -- From spiritual liberty to sexual license -- Cultivating land, cultivating families -- Civilizing domesticity -- Revival, rebellions, and colonial subordination